AIF and Scythe (Bat3) Regulate Phosphatidylserine Exposure and Macrophage Clearance of Cells Undergoing Fas (APO-1)-Mediated Apoptosis - Preta, Giulio (Public Library of Science, 2012)
Phosphatidylserine (PS) exposure on the cell surface has been considered a characteristic feature of apoptosis and serves as a molecular cue for engulfment of dying cells by phagocytes. However, the mechanism of PS exposure is still not fully elucidated. Here we show that the cytosolic release from mitochondria of apoptosis-inducing factor (AIF) is required for PS exposure during death receptor-induced apoptosis and for efficient clearance of cell corpses by primary human macrophages. Fas-triggered PS exposure was significantly reduced upon siRNA-mediated silencing of AIF expression and by inhibition of the cytosolic translocation of AIF. In addition, AIF localizes to the plasma membrane upon Fas ligation and promotes activation of phospholipid scrambling activity. Finally, cytosolic stabilization of AIF through interaction with Scythe is shown to be involved in apoptotic PS exposure. Taken together, our results suggest an essential role for AIF and its binding partner Scythe in the pathway leading to apoptotic corpse clearance.